Сто великих политиков - Соколов Борис Вадимович (100 великих, 2010)
На обл. авт. не указан Экземпляры: ф.7 (2010) / Инвентарный номер: 53338 / Цена: / Сис.шифр: 63.3(0) / Авт.знак: С 59 / ГРНТИ: 03 / ББК: 63.3(0)